Strategic planning: a practice perspective - Langley, Ann (Henry Stewart Talks, 2014)
What is “strategic planning”?, Early and more current research on strategic planning, A framework for strategic planning, Strategic planning as a social practice (Textual practices, Production practices, Consumption practices, Temporal dynamics), Evolution of planning systems, Multiple opportunities for further research
Reviewed at 2018/02/28